THE EFFECT OF STUDY DISCIPLINE, STUDY HABITS, STUDY FACILITIES, LEARNING STYLES, AND PARENTAL ROLE ON LEARNING ACHIEVEMENT IN ECONOMICS CLASS XI PHASE F AT SMAN 2 LUBUK SIKAPING - Mulyadi, Jefri; Vivina Eprillison; Dina Amaluis (Global Action and Education for Society, 2025)
This study aims to analyze 1) the effect of learning discipline on academic achievement, 2) the effect of learning habits on academic achievement, 3) learning facilities on academic achievement, 4) the effect of learning style on academic achievement, 5) the effect of parental role on academic achievement, (6) the combined influence of study discipline, study habits, learning facilities, learning style, and parental role on the academic achievement of Grade XI Fase F students at SMAN 2 Lubuk Sikaping. This study is a descriptive and associative research. The population in this study was grade XI students, namely XI F 1, XI F 2, and XI F 3 in the 2024/2025 academic year, totaling 101 students. Sampling was conducted using the proportionate random sampling technique. The research was conducted in August. The instruments used for the research were closed-ended questionnaires, with the use of Multiple Linear Regression Analysis and hypothesis testing using t-tests and F-tests. The results of the research indicate that: First, there is a significant influence between study discipline and academic achievement, with a coefficient value of -0.210, a t-value of -4.913 < t-table value of 1.992; Second, there is a significant influence between study habits and academic achievement with a coefficient value of 0.208, a t-value of 5.393 > t-table of 1.992; Third, there is a significant influence between learning facilities and academic achievement with a coefficient value of 0.386, a t-value of 7.929 > t-table of 1.992; Fourth, there is a significant influence between learning style and academic achievement with a coefficient value of -0.189 and a t-value of -4.157 < t-table of 1.992; Fifth, there is a significant influence between parental role and student learning achievement with a coefficient value of -0.104 and a t-value of -5.095 > t-table value of 1.992; Sixth, there is a significant influence of learning discipline, learning habits, learning facilities, learning style, and parental role together on student academic achievement with Fcount28.759 > Ftable 2.34.